Neuroticism modulates functional connectivity of the midcingulate cortex during emotional conflict - Hakin Kim; Junhyun Park; Manuel Kuhn; M. Justin Kim; Juyoen Hur (Scientific Reports)
Abstract Neuroticism (NT) is a fundamental personality trait and a major risk factor for both the onset and persistence of depression and anxiety disorders. Although NT involves alterations in emotion–cognition interaction, its precise neural mechanism remains insufficiently understood. Leveraging the word-face Stroop task, we examined neural circuits engaged during emotional conflict using a relatively large sample that exhibited a wide range of NT levels. Generalized psychophysiological interaction (gPPI) analyses revealed that individuals with high NT were characterized by decreased functional connectivity between the anterior midcingulate cortex (aMCC) and both the left dorsolateral prefrontal cortex (dlPFC) and the left amygdala. None of these regions showed modulated brain activation by NT. Our findings suggest that the neural substrates of NT can be better characterized by reduced top-down aMCC-amygdala regulation as well as inefficient communication within the dorsal cognitive system (aMCC-dlPFC), rather than changes in brain activation in isolated regions. These observations offer valuable insights into the neural markers of vulnerability to mood and anxiety disorders.